Muscarinic receptor activation in colon cancer selectively augments pro-proliferative microRNA-21, microRNA-221 and microRNA-222 expression. - Shannon M Larabee; Kunrong Cheng; Jean-Pierre Raufman; Shien Hu (PLoS ONE, 2022)
Overexpression of M3 subtype muscarinic receptors (M3R) hastens colon cancer progression. As microRNA (miRNA) expression is commonly dysregulated in cancer, we used microarrays to examine miRNA profiles in muscarinic receptor agonist-treated human colon cancer cells. We used quantitative RT-PCR (qPCR) to validate microarray results and examine miRNA expression in colon cancers and adjacent normal colon. These assays revealed that acetylcholine (ACh) treatment robustly induced miR-222 expression; miR-222 levels were three-fold higher in cancer compared to normal colon. In kinetic studies, ACh induced a 4.6-fold increase in pri-miR-222 levels within 1 h, while mature miR-222 increased gradually to 1.8-fold within 4 h. To identify post-M3R signaling mediating these actions, we used chemical inhibitors and agonists. ACh-induced increases in pri-miR-222 were attenuated by pre-incubating cells with atropine and inhibitors of protein kinase C (PKC) and p38 MAPK. Treatment with a PKC agonist, phorbol 12-myristate 13-acetate, increased pri-miR-222 levels, an effect blocked by PKC and p38 MAPK inhibitors, but not by atropine. Notably, treatment with ACh or transfection with miR-222 mimics increased cell proliferation; atropine blocked the effects of ACh but not miR-222. These findings identify a novel mechanism whereby post-M3R PKC/p38 MAPK signaling stimulates miR-222 expression and colon cancer cell proliferation.